Macroeconomic Determinants of Exchange Rate Dynamics in Nigeria - Obuareghe, Goddey; Orubu, Christopher O.; Awogbemi, Titus O. (PT. Riset Press International, 2025)
The study examined Nigeria's macroeconomic determinants of exchange rate dynamics over thirty-seven years, from 1986 to 2022. The major data sources are the Central Bank of Nigeria Statistical Bulletin, the Nigerian Bureau of Statistics, World Bank Development Indicator, the Organization of Petroleum Exporting Countries, the U.S Federal Reserve Bank, and other relevant literature. The study adopted the structural Vector Autoregressive (VAR) estimate to test the responses of exchange rates. Other estimation techniques considered are Impulse Response Function and Variance Decomposition Test. The study reported that past exchange rate (EXCR) values respond positively to an increase in innovation shock, and the response is statistically significant up to the second horizon. More so, past values of broad money supply and changes in crude oil prices positively impact the exchange rate. However, the study affirmed that past government capital expenditure and trade openness values are statistically insignificant but positively impact the exchange rate. Again, exchange rates respond speedily to changes in broad money supply, government expenditure, oil price fluctuation, degree of trade openness, and inflation rate. Hence, the study concludes that past values of broad money supply, government capital expenditure, changes in crude prices, and inflation rates are major macroeconomic determinants of the exchange rate in Nigeria. As such, the study submits that policymakers are to pay close attention to the rising rate at which more money is outside the shores of the Nigerian banking industry. Lastly, more federal government expenditures should be allocated to capital expenditure.